Cover Picture: In vivo CT imaging tracking of stem cells labeled with Au nanoparticles (View 3/2022). Issue 3 (30th May 2022) - Huang, Jie; Bao, Hongying; Li, Xiaodi; Zhang, Zhijun
Abstract : Computed tomography (CT) provides a noninvasive, sensitive and real‐time imaging and tracking tool for monitoring and in‐depth understanding of delivery, migration, and final fate of transplanted stem cells in regenerative medicine and other biomedical applications. In article number 20200119, Jie Huang and coworkers present an overview of the recent progress in gold nanoparticle (AuNP)‐based CT imaging tracking of stem cells, with focuses on new strategies to improve cellular uptake of AuNPs for better CT imaging contrast, and on multimodal imaging tracking of stem cells in vivo. Finally, they discuss major challenges and possible future directions of the research.